Long term effects of anti-VEGF agents: patho-physiological perspectives - Gupta, M; Gupta, Y; Phougat, A (Nepalese Journal of Ophthalmology, 2013)
Monoclonal antibodies directed against different targets have become a new tool for the treatment of various disorders. More than 20 monoclonal antibody-based therapies have been approved in the USA and hundreds more are in development. Some of these therapies are finding applications in ocular disorders. The role of anti-VEGF in the treatment of wet ARMD is now well known. Anti-VEGF, which were initially discovered to treat carcinomas like bevacizumab in metastatic colorectal carcinoma, have now found place in ophthalmology to treat disorders where neovascularization/angiogenesis leads to blindnes. Nepal J Ophthalmol 2013; 5(9):100-105 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7834